Sampling Protocols: Version 5 - Legacy, The Nansen (The Nansen Legacy Report Series, 2020)
The collection of detailed sampling protocols is crucial tool for the success of the Nansen Legacy, because they ensure:• Methodological agreement between the involved researchers• Continuity and comparable data throughout the 5 years sampling period• An easily accessible overview over parameters sampled• Easier cruise planning